Britten's Death in Venice Deborah Warner (stage director), Edward Gardner (conductor) - wth John Graham-Hall (Gustav von Aschenbach) - English National Opera - Mann, Thomas 1875-1955; Britten, Benjamin 1913-1976 (Leopard Films, 2013)
At the English National Opera, Deborah Warner has been directing Benjamin Britten's final opera, Death in Venice, conducted by Edward Gardner. Death in Venice, the last opera by Benjamin Britten, was composed based on the novella by Thomas Mann of the same name, which inspired at least one other celebrated artist, the filmmaker Luchino Visconti. Britten's opera was first performed at Aldeburgh Festival in 1973, just two years after the cinema release of Visconti's film, which Britten never saw. The complicated subject of the opera required a lot of preparation. Britten, who was already very ill, often expressed his fear that he would not be able to finish it. He even postponed an important operation in order to finish the score. Despite his best efforts, he was not able to conduct his piece, neither for its first performance, which he heard on the radio, nor for its recording.
Title from Medici.tv website
Opera in two acts
Filmed for a live telecast by Sky Arts 2
Based on the novella by Thomas Mann
Keywords: Older gay men; Operas; Older gay men -- Drama; Venice (Italy) / Drama; Italy / Venice; Cultural television programs; Internet videos; Drama; Filmed performances